2023
DOI: 10.1001/jama.2023.17607
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review and Scientific Publication at a Crossroads

John P. A. Ioannidis,
Michael Berkwits,
Annette Flanagin
et al.

Abstract: The way science is assessed, published, and disseminated has markedly changed since 1986, when the launch of a new Congress focused on the science of peer review was first announced. There have been 9 International Peer Review Congresses since 1989, typically running on an every-4-year cycle, and most recently in 2022 after a 1-year delay due to the COVID-19 pandemic. 1 Here, we announce that the 10th International Congress on Peer Review and Scientific Publication will be held in Chicago, Illinois, on Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…9 The pandemic demonstrated that current technology has transformed the possible speed of research production, synthesis and dissemination. 11 Given the prospect of such an acceleration, the acceptability of a 5-or 10-year delay in producing a 'strong' clinically important recommendation is unlikely to hold.…”
Section: The Covid Revelationsmentioning
confidence: 99%
“…9 The pandemic demonstrated that current technology has transformed the possible speed of research production, synthesis and dissemination. 11 Given the prospect of such an acceleration, the acceptability of a 5-or 10-year delay in producing a 'strong' clinically important recommendation is unlikely to hold.…”
Section: The Covid Revelationsmentioning
confidence: 99%
“…Using reporting guidelines, such as the CONsolidated Standards of Reporting Trials (CONSORT), can improve trial reporting standards [68], but adherence is often poor [9]. Following recent calls to evaluate the role of Artificial Intelligence (AI) in facilitating editorial and peer review decisions [10], we assessed how well an AI model could determine reporting guideline adherence in clinical trial reports.…”
Section: Introductionmentioning
confidence: 99%
“…The 10th International Congress on Peer Review and Scientific Publication, announced to be held in Chicago, Illinois, on 3-5 September 2025, will be a great opportunity to share proposals and solutions to make peer review, [31]. We welcome contribution from interested journals dealing with pharmacovigilance to pursue this call towards an effective innovative model of peer review.…”
mentioning
confidence: 99%